Fish landing management Fishery Port of Palabuhanratu West Java province - Daud Hasian Joel; Jonny Zain; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in March until April 2017 at Fishery Portof Nusantara Palabuhanratu West Java Province. The purpose of this research is toknow the cause of difference of fish landing implementation in PPNPalabuhanratu with guidance of fishery landing fishery management ofDirectorate of Infrastructure. The method used in this research is survey method,that is by observing the elements - elements and management functions associatedwith fish landing facilities and activities in the VAT Palabuhanratu. From theresults of the research indicate that there are differences in the implementation offish landing activity in the VAT Palabuhanratu with guidance of fish landingmethod Directorate of Infrastructure Development. First, the ships that will bedocked will be given the queue number and the officer determines the demolitionsite, but the ship is closing its vessel on the dock unloading without thesupervision of the port officer. Secondly, the ship landed the fish at the frontloading pier of TPI and when it was completed the demolition of the vessel wassupposed to be transferred to the boat mooring dock, but that happened finishedunloading the catch, the ship was not directly transferred to the parking lot of theship, but parked his ship on the dock Unloading it. So the other vessels do thedemolition at the mooring dock.Keywords: Fish Landing, Management, Palabuhanratu